(untitled) (International Journal of Emerging Trends in Science and Technology, 2017)
Urbanization is an index of transformation from traditional rural economies to modern industrial one. Urbanization is a Progressive concentration of population in urban unit (Kingsley Davis1965). Urbanization, or the shift of population from rural to urban environments, is a transitory process. Accepting urbanization as a conscious and conditioned adjustment of societies to their changing environment, the present study describes the Emerging Pattern of Urbanization in Haryana. The study is based on district level secondary data from the 2011 census of India. Presently, Haryana State represents about 34.9 per cent urban population to total population. The study shows that districts Panchkula, Faridabad and Gurgaon, were highly urbanized. The results obtained from processing of data are presented in the form of line graph, tables and choropleth maps.